1988
DOI: 10.1016/0735-1097(88)90400-7
|View full text |Cite
|
Sign up to set email alerts
|

Change in diameter of coronary artery segments adjacent to stenosis after percutaneous transluminal coronary angioplasty: Failure of percent diameter stenosis measurement to reflect morphologic changes induced by balloon dilation

Abstract: To determine the changes in stenotic and nonstenotic segments of a dilated coronary artery, detailed quantitative angiographic measurements were performed in 342 patients (398 lesions) immediately after angioplasty and at a predetermined follow-up time of 30, 60, 90 or 120 days after the dilation. Measurements of the stenotic segments were expressed as minimal luminal diameter, and the adjacent nonstenotic segments were expressed as interpolated reference diameter (both in millimeters). A follow-up rate of 86%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
4

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 26 publications
1
12
0
4
Order By: Relevance
“…It has been reported that some degree of late loss occurs even for nonrestenotic lesions after percutaneous interventions with bare stents. 1,7 In a previous study with conventional stenting, Schomig et al 7 have shown that lesions in the lower range of lumen renarrowing still presented a late lumen loss of Ϸ0.5 mm, a number similar to that observed in our control group. SES implantation, however, has been shown in our series to virtually abolish neointimal formation in nonrestenotic lesions.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It has been reported that some degree of late loss occurs even for nonrestenotic lesions after percutaneous interventions with bare stents. 1,7 In a previous study with conventional stenting, Schomig et al 7 have shown that lesions in the lower range of lumen renarrowing still presented a late lumen loss of Ϸ0.5 mm, a number similar to that observed in our control group. SES implantation, however, has been shown in our series to virtually abolish neointimal formation in nonrestenotic lesions.…”
Section: Discussionsupporting
confidence: 85%
“…However, it remains a matter of debate whether restenosis simply represents an extreme form of the "normal" vessel healing response after mechanical dilatation or if it is related to specific mechanisms that ultimately lead to vessel renarrowing. [1][2][3][4][5][6][7] Although several cutoff criteria have been proposed to dichotomize patients with restenosis from those without restenosis, it has been widely recognized that, to some extent, late luminal reduction is a ubiquitous phenomenon, occurring even in those categorized as not having binary restenosis. 1,7 Recently, drug-eluting stents with the antiproliferative agent sirolimus have proved to reduce neointimal growth markedly in clinical trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There may be no view which shows the long axis of the artery, or there may be poor or nonuniform filling and failure to center the artery. Yet the necessity for an objective, repeatable method of analyz ing cinefilms of coronary arteriograms is of increasing importance in order to assess the effects of various mechanical interventions, such as balloon angioplasty, and the effects of newly available medications, which have the potential to modify progression or to result in regression of coronary artery lesions [ 12-l 4], To date, attempts to measure changes in coronary artery' stenoses following PTCA, us ing automated edge detection techniques, have encountered many pitfalls [15], as changes in the contour of the normal segment may occur following PTCA. In addition, bor der recognition techniques require consider able operator interaction in the setting of PTCA in order to distinguish between true flow channels and blind pouches created as a result of the angioplasty [ 16].…”
Section: Discussionmentioning
confidence: 99%
“…Este espessamento intimal é uma característica da resposta da parede vascular à injúria e ocorre independentemente da técnica de angioplastia utilizada 6,7 . Histologicamente, a hiperplasia da íntima difere significativamente da placa aterosclerótica, quanto à arquitetura celular e ao conteúdo lipídico.…”
Section: A Hiperplasia Da íNtimaunclassified